EKSTRAKSI LEMAK DARI BIJI TENGKAWANG TUNGKUL (SHOREA STENOPTERA BURCK) DENGAN BEBERAPA PELARUT ORGANIK - Bambang Wiyono (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
The purpose of this research is to study the effect of several organic solvents and storage time on fat content, acidify, and free fatty acid content of Illipe nut hernels (S. stenoptera Burck). The treatment effect was analysed by using a randomized complete block design.The result indicated that storage time reduced moisture content of Illipe nut kernels (S. stenoptera Burck), but on the contrary the storage treatment tended to increased the ash content. Extended storage time decreased fat content significantly. Acetone solvent extraction produced highly significantly effect on fat and free fatty acid content than that of the other solvents. Biochemical activity of lllipe nut hernels (S. stenoptera Burck) degraded the quality, and the rate of degradation was influenced by humidity and temperature. Therefore, to maintain. good kernels quality, optimum storage condition is desired.